Assessment of consumers’ preference for orange-fleshed sweet potato puree chapati: a case of rural and urban consumers in Kenya - Owuor, Antonate Akinyi; Otieno, David Jakinda; Okello, J.J.; Oluoch-Kosura, Willis; Dufour, D. (Wiley, 2024)
Background Orange-fleshed sweetpotato (OFSP) is bio-fortified with vitamin A precursors through breeding and is thus ideal for combating vitamin A deficiency (VAD). One of the potential mechanisms to promote the consumption of OFSP is to enhance its availability through processing into products with a longer shelf life and more desirable to consumers. However, very few farmers and agro-processors practice value addition due to market uncertainties; there is little information on market availability for OFSP products. This study examined consumers’ preference for OFSP puree chapati in rural and urban areas of Kenya, using the contingent valuation method. Data was collected from a random sample of 411 sweetpotato consumers and a double-bounded logit model was applied to analyze consumers’ willingness to pay (WTP) for OFSP puree chapati.